Madrasah accreditation assistance to improve education quality - Erni Triani (Community Empowerment, 2022)
Teachers' perceptions of accreditation are still primarily based on tangible objects or written evidence. Accreditation, however, emphasizes performance assessment. The lack of updating of teacher learning tools documents that refer to 21st century skills cause the low quality of learning and is still lower order thinking skills (LOTS). The purpose of this program is to improve teachers' comprehension of the performance-based accreditation paradigm. Utilizing a three-stage process of socialization, training, and mentoring, this activity employs a participatory rural appraisal approach. With the implementation of this program, evidence of the four components of the accreditation of MTs Muhammadiyah 1 Dukun can be fulfilled and teachers are able to make teaching aids and master the media so that learning can be more meaningful. Another result of this training is that teachers are able to develop learning tools that are higher order thinking skills (HOTS).